Use of Moringa oleifera seed extracts to reduce helminth egg numbers and turbidity in irrigation water - Sengupta, M.E.; Keraita, Bernard N.; Olsen, A.; Boateng, Osei K.; Thamsborg, S.M.; Palsdottir, G.R.; Dalsgaard, A. (Elsevier, 2012)
Water from wastewater-polluted streams and dug-outs is the most commonly used water source for irrigation in urban farming in Ghana, but helminth parasite eggs in the water represent health risks when used for crop production. Conventional water treatment is expensive, requires advanced technology and often breaks down in less developed countries so low cost interventions are needed. Field and laboratory based trials were carried out in order to investigate the effect of the natural coagulant Moringa oleifera (MO) seed extracts in reducing helminh eggs and turbidity in irrigation water, turbid water, wastewater and tap water. In medium to high turbid water MO extracts were effective in reducing the number of helminth eggs by 94e99.5% to 1e2 eggs per litre and the turbidity to 7e11 NTU which is an 85e96% reduction. MO is readily available in many tropical countries and can be used by farmers to treat high turbid water for irrigation, however, additional improvements of water quality, e.g. by sand filtration, is suggested to meet the guideline value of 1 helminth egg per litre and a turbidity of 2 NTU as recommended by the World Health Organization and the U.S. Environmental Protection Agency for water intended for irrigation. A positive correlation was established between reduction in turbidity and helminth eggs in irrigation water, turbid water and wastewater treated with MO. This indicates that helminth eggs attach to suspended particles and/or flocs facilitated by MO in the water, and that turbidity and helminth eggs are reduced with the settling flocs. However, more experiments with water samples containing naturally occurring helminth eggs are needed to establish whether turbidity can be used as a proxy for helminth eggs.